Digital Immigrant EFL Teachers’ Experiences in the Early Phase of Shifting From Offline to Online Learning: A Case Study - Dela Sherly Aprilina; Salim Nabhan (Jurnal Pendidikan Bahasa, 2022)
The shifting of classroom instruction from face-to-face to online learning is inevitable due to the Pandemic. The condition has forced teachers to adapt to educational technology, especially digital immigrant EFL teachers who are not, in general, familiar with the digital technology. Not much research has been done regarding the experiences of digital immigrant EFL teachers, the challenges of digital immigrant EFL teachers, and how digital immigrant EFL teachers adapt in the early phase of the transition from offline to online learning. Therefore, this study aims to investigate the experiences and adaptation of digital immigrant EFL teachers in the early phase of the transition from offline to online learning. Qualitative research in the form of a case study was used as a research approach. The researchers took the data from interviews, observations, and documents. There were two English teachers as respondents in this study. The data obtained from the interviews were then transcribed verbatim and analyzed using thematic analysis. The current study shows that there are two main themes as findings to be discussed; Digital immigrant EFL teacher experiences at the beginning of offline to online learning, and how Digital immigrant EFL teachers adapt to teaching online. Most Digital Immigrant EFL teachers had different ways of adaptation. However, the difficulties in online teaching were able to be managed since teachers were constantly learning to improve their digital literacy. This study might have implications for the understanding of the practices of digital immigrant EFL teachers in the context of teachers’ professional development